Multisensory Mediation for Visitors with ASD and Other Mental Disorders in Museums - E.I. Kiseleva-Afflerbach (Moscow State University of Psychology and Education, 2022)
The development of inclusive activities in Russian museums today presumes an active rethinking of the visitor-interaction, including kids and adults with autism spectrum condition (ASС) and other developmental disabilities. The development of inclusive activities in Russian museums today presumes an active rethinking of the visitor-interaction, including kids and adults with autism spectrum disorders and other developmental disabilities. Museums make great efforts to create an open and friendly environment for children and adults with reduced sensory threshold. This text presents the Accessible Museum program experience by The Pushkin State Museum of Fine Arts, which is largely focused on the space, collections and program accessibility. Multisensory approach including sound, smell, touch, movement and other bodily experience belongs to the new challenges of visitor experience development in the Pushkin Museum. The article offers review of the projects using multisensory communication in Russian and international museums over the past ten years, when there has been a significant expansion of inclusive practices.